﻿Contribution to the microscopic identification of Zingiber officinale - Anna Gavrilova; Genadi Gavrilov; Dora Trifonova (Pensoft Publishers, 2022)
Zingiber officinale Roscoe has a very long history of use throughout the world, both as a spice and as a medicinal plant. During the last two years in the midst of a global pandemic of SARS-CoV-2 the use of various herbal products with ginger rhizome as active ingredient increased because of its numerous health beneficial properties. A detailed characteristic of the crude powdered drug is presented by microscopic photographs for the first time. Although the structure of ginger rhizome is relatively simple and well-studied, the presented results in combination with the detailed analysis of the literature provide additional insight to the pharmacopoeial guidelines for the identification of ginger powder.